THE ANALYSIS OF STUDENTS’ CRITICAL THINKING IN ONLINE DISCUSSION FORUM BY USING SCHOOLOGY IN SPEAKING B CLASS OF FIRST SEMESTER STUDENTS OF FKIP UBL - Sidabalok, Dameria Magdalena; Fitriana, Sela (Universitas Bandar Lampung, 2018)
Online discussion forum is well-known in educational technology development especially in blended learning because it supports the traditional face to face (f2f) classroom. Moreover, online discussion forum is familiar as the leading of critical thinking process. Therefore, this present study is intended to analyze the influence of critical thinking to help improving speaking skill of the first semester students in Universitas Bandar Lampung. To achieve the goal, online discussion forum is provided to promote critical thinking through Schoology platform. A qualitative approach is employed to analyze the data. Observation, interview, and questionnaire are conducted to see the influence of critical thinking process during online discussion forum, and the influence of critical thinking to improve students? speaking skill. The finding indicates that the use of online discussion forum can promote students? critical thinking, and the students can perform better in the f2f classroom